Fullerene fine particles adhere to pollen grains and affect their autofluorescence and germination - Aoyagi H (Dove Medical Press, 2011)
Hideki Aoyagi, Charles U UgwuLife Science and Bioengineering, Graduate School of Life and Environmental Sciences, University of Tsukuba, Tsukuba, JapanAbstract: Adhesion of commercially produced fullerene fine particles to Cryptomeria japonica, Chamaecyparis obtusa and Camellia japonica pollen grains was investigated. The autofluorescence of pollen grains was affected by the adhesion of fullerene fine particles to the pollen grains. The degree of adhesion of fullerene fine particles to the pollen grains varied depending on the type of fullerene. Furthermore, germination of Camellia japonica pollen grains was inhibited by the adhesion of fullerene fine particles.Keywords: Cryptomeria japonica, Chamaecyparis obtusa, Camellia japonica, autofluorescence, pollen grains, fullerene fine particle